The Epidemiology of Chronic Suppurative Lung Disease and Bronchiectasis in Children and Adolescents - McCallum, Gabrielle B.; Binks, Michael J. (Frontiers in Pediatrics, 2017)
In the modern era, the global burden of childhood chronic suppurative lung disease (CSLD) remains poorly captured by the literature. What is clear, however, is that CSLD is essentially a disease of poverty. Disadvantaged children from indigenous and low and middle income populations had a substantially higher burden of CSLD, generally infectious in aetiology and of a more severe nature, than children in high income countries. A universal issue was the delay in diagnosis and the inconsistent reporting of clinical features. Importantly, infection related CSLD is largely preventable. A considerable research and clinical effort is needed to identify modifiable risk factors and socioeconomic determinants of CSLD and provide robust evidence to guide optimal prevention and management strategies. The purpose of this review was to update the international literature on the epidemiology, aetiology and clinical features of paediatric CSLD.